2005
DOI: 10.1111/j.1525-1470.2005.22109.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Disseminated Juvenile Xanthogranulomatosis Benign Cephalic Histiocytosis?

Abstract: We describe an infant with a congenital form of non-Langerhans cell histiocytosis with clinical and pathologic features of both disseminated juvenile xanthogranulomatosis and benign cephalic histiocytosis. The findings in this case support the concept of these non-Langerhans cell histiocytoses forming part of a spectrum of disease rather than being separate pathologic entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
(31 reference statements)
1
26
0
1
Order By: Relevance
“…BCH must primarily be differentiated from micronodular form of JXG and GEH6,8. Furthermore, LCH, plane warts, urticaria pigmentosa, lichenoid sarcoidosis and multiple Spitz nevi can be confused with BCH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCH must primarily be differentiated from micronodular form of JXG and GEH6,8. Furthermore, LCH, plane warts, urticaria pigmentosa, lichenoid sarcoidosis and multiple Spitz nevi can be confused with BCH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extracutaneous involvement occurs most significantly in the eyes. Histologic examination shows foamy cells and Touton giant cells8,9. GEH is more common in adults, with a more extensive distribution of lesions and occasional mucosal involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation of BCH lesions into JXG has been reported in 2 infants, aged 6 months6 and 1 year7, respectively. In addition, Sidwell et al reported a case of simultaneous occurrence of disseminated JXG and BCH8. These findings can be interpreted as being supportive of the hypothesis that BCH and JXG are different morphologic expressions of the same disease.…”
Section: Discussionmentioning
confidence: 65%
“…Spontaneous regression of the eruption is the rule; complete regression occurs within 50 months, on average. However, recent studies have suggested an association of BCH with other non-Langerhans cell histiocytosis disorders, and BCH is now regarded as a part of non-Langerhans cell histiocytosis in its clinical spectrum5-8. In general, BCH does not lead to abnormalities in laboratory test results, or have known complications.…”
Section: Discussionmentioning
confidence: 99%